Deformation theory analysis of a dynamically loaded rigid-plastic cantilever - Liebenberg, Franciscus Xavierius (Department of Civil Engineering, 2016)
Taya and Mura (1974) introduced a new thought into rigid-plastic approximate methods by presenting what was claimed to be an extension of Hamilton's Principle (normally considered to be restricted to conservative systems) to rigid-plastic structural dynamics. A comment by Professor A.R.S. Ponter, however, has led to the present study. Professor Ponter queried whether Taya and Mura had indeed extended Hamilton's Principle; it could equally well be interpreted that in the limited applications which they considered they had replaced the usual non-holonomic viscous rigid-plastic relation by a holonomic deformation theory or non-linear elastic relation. This interpretation can be made because Taya and Mura did not consider any applications in which unloading took place.